Hyperuricemia reduces the risk of MCI but not dementia: a cross-sectional study in Liuyang - He, Yong; Zhu, Tieshi; Bei, Erxinxian; Xiang, Guangpeng; Xi, Danyang; Meng, Heng; Bei, Yuzhang (Frontiers in Neurology, 2025)
BackgroundCognitive impairments, including mild cognitive impairment (MCI) and dementia, significantly affect patients’ daily functions and quality of life, contributing to a substantial societal and economic burden. The role of uric acid in cognitive function is controversial, with some studies suggesting protective effects, while others indicate increased risk of cognitive decline.MethodsA total of 1,098 participants with an average age of 69 years were included in the study. Cognitive function was assessed using the Mini-Mental State Examination. Hyperuricemia was defined as blood uric acid concentrations >420 μmol/L. Logistic regression and restricted cubic spline analysis were performed to assess the association between hyperuricemia and cognitive impairment, including MCI and dementia.ResultsHyperuricemia was associated with a lower risk of cognitive impairment (OR = 0.51, 95% CI = 0.31–0.80) and MCI (OR = 0.39, 95% CI = 0.21–0.69), particularly in individuals younger than 70 years, males, and those without hypertension or diabetes. No significant association was found between hyperuricemia and dementia (OR = 0.94, 95% CI = 0.44–1.89). There is no evidence of a non-linear relationship between hyperuricemia and cognitive impairment.ConclusionHyperuricemia appears to have a protective effect on cognitive function, particularly in reducing the risk of MCI, but not dementia, in specific populations.